Staphylococcal Bacterial Persister Cells, Biofilms, and Intracellular Infection Are Disrupted by JD1, a Membrane-Damaging Small Molecule - Jamie L. Dombach (American Society for Microbiology, 2021)
Untreatable bacterial infections are a critical public health care issue. In addition to increasing antibiotic resistance, bacteria that are in slow-growing or nongrowing states, or that live inside mammalian cells, are typically insensitive to clinical antibiotics and therefore difficult to eradicate.